PERLINDUNGAN HUKUM DAN TANGGUNG JAWAB TERHADAP PENUMPANG SIPIL PADA KECELAKAAN PESAWAT UDARA DALAM LINGKUP HUKUM INTERNASIONAL - Febri Dermawan; Sutiarnoto Sutiarnoto; Chairul Bariah (Journal of USU International Law, 2013)
Abstract The writing is on the backs by setting the legal protection and responsibilities of civil passenger aircraft accident within the scope of international law, the problem is how the civil aviation, legal protection of civilian passengers, airline liability for passenger aircraft accidents. It is necessary to set up an arrangement of the flight. But in reality the calamities that befall the flight is still occurring, then get out some of the Convention among other Warsawa Convention of 1929, Act No. 1 of 2009. Keywords : legal protection, responsibility, aircraft accident